RUMPUT LAUT: ANTIOKSIDAN ALAMI PENANGKAL RADIKAL BEBAS - Rany Dwimayasanti (Pusat Penelitian Oseanografi LIPI, 2018)
SEAWEED: NATURAL ANTIOXIDANT FREE RADICAL ANTIDOTE. Free radicals are the result of various complex chemical processes in the body, in form of oxidation process, cell metabolism, UV irradiation, environmental pollution such as cigarette smoke, and other pollutants. The effects of free radicals can be prevented by addition of antioxidants endogenously from outside the body. Seaweed is one source of natural antioxidants that is safe for the body. Seaweed contains bioactive compounds that are able to prevent free radicals such as carotenoids, phenols, vitamins and minerals.